Examination of the relationship between dominant & non-dominant isokinetic knee strength and the body composition in basketball players - Pekel, H. A.; Cengizel, Ç. Ö. (International Journal of Applied Exercise Physiology, 2020)
The objectives of this study are (a) the comparison of dominant and non-dominant knee strength (b) the determination of body compositionand comparison of dominant vs. non-dominant leg composition and (c) the determination of the relationship between isokinetic strength and the body composition in basketball. 21 male basketball players from the senior category voluntarily participated in the study. Isokinetic knee strength of the subjects was performed at three different angular speeds (60 °/sec 5 rep, 180 °/sec 10 rep, 300 °/sec 20 rep) in knee flexion (Hamstring: H) and extension (Quadriceps: Q). The body composition was determined using a bioimpedance analyzer. A significant difference was found in the dominant and non-dominant knee strength of the subjects and the power parameters at 60 °/sec & 180 °/sec angular speed (p<0.05). The most significant bilateral force difference is found at an angular speed of 60 °/sec, while isokinetic knee strength parameters at 300 °/sec angular speed are not different for the dominant and non-dominant sides. Dominant vs. non-dominant leg composition (fat percentage, fat mass, fat-free mass, predicted muscle mass) was not significantly different. However, a significant positive correlation was determined between the subjects' body weight, fat-free muscle mass, fat-free leg muscle mass and predicted leg muscle mass and isokinetic knee strength. As a result, although there is no difference in dominant vs. non-dominant leg composition in elite male basketball players, there is a difference in isokinetic knee strength. Especially in less repetitive and explosive exercises (such as jumping), this difference is greater.Besides, it is predicted that when fat-free body&leg mass and muscle mass are increased, isokinetic knee strength will also increase. Therefore, to prevent injuries, it is recommended to include exercises that will increase leg muscle mass to minimize or eliminate the difference in bilateral isokinetic knee strength and to increase the jump height.